Management and School Culture. Analytical References About Educational Reform - Pérez Ruiz, Abel (2013)
This paper discusses some points of articulation between the management and the school culture as a path to advance in understanding of the real operation of the schools in contrasting and complex contexts. In this perspective, it is recognized that inside the centers are configured historically cultural codes, which maintain a dialectical relationship with the instrumentation of a policy, program or a plan of emerging nature oriented to the improvement of processes. The management and the school culture, therefore, form a central element of attention to investigate the different behaviors associated to the imperatives currently in progress relating to the quality, innovation, efficiency; which influence the practices of those who have the responsibility to carry out the emerging commitments of the education.